What should Common Core assessments measure?. (February 2016) - Chandler, Kayla; Fortune, Nicholas; Lovett, Jennifer N.; Scherrer, Jimmy
The Common Core State Standards for mathematics promote ideals about learning mathematics by providing specific standards focused on conceptual understanding and incorporating practices in which students must participate to develop conceptual understanding. Thus, how we define learning is pivotal because our current definition isn't aligned with how we teach and assess. But how do we reconcile the two? What does this look like? And what does this imply about how we assess learning?